Legal silo's and indifference: the wrongful prosecution of refugees and asylum-seekers in the UK. (23rd March 2022) - Campbell, John R.
This paper explores the situation in the UK where the government has consistently prosecuted and convicted asylum-seekers who have entered the country in contravention of its obligations under Art. 31(1) of the 1951 Refugee Convention . This paper examines the history of these prosecutions and the UK's criminal justice system and the UK's asylum and immigration system in handled these cases. At the centre of the CJS lies the Criminal Cases Review Commission which reviews wrongful convictions, and the criminal court of appeal which can quash wrongful convictions. The paper concludes that there are three major reasons why asylum seekers continue to be prosecuted and convicted: 1) only a 'patchwork' of protections exists to protect asylum-seekers from prosecution; 2) all state/legal institutions operate in policy silos and fail to communicate with one another; 3) legal institutions are indifferent to and deeply hostile towards asylum-seekers.